Impact of mitochondria on local calcium release in murine sinoatrial nodal cells. (March 2022) - Takeda, Yukari; Matsuoka, Satoshi
Abstract: Roles of mitochondria in sinoatrial nodal cells (SANCs) have not been fully clarified. We have previously demonstrated that mitochondrial Ca 2+ efflux through the Na + -Ca 2+ exchanger, NCXm, modulates sarcoplasmic reticulum (SR) Ca 2+ content and automaticity of HL-1 cardiomyocytes. In this study, we extended this line of investigation to clarify the spatial and functional association between mitochondria and local calcium release (LCR) from the SR in murine SANCs. High-speed two dimensional (2D) and confocal line-scan imaging of SANCs revealed that LCRs in the early phase of the Ca 2+ transient cycle length (CL) appeared with a higher probability near mitochondria. Although LCR increased toward the late phase of CL, no significant difference was noted in the occurrence of late LCRs near and distant from mitochondria. LCRs, especially in the late phase of CL, induced temporal and spatial heterogeneity of the Ca 2+ transient amplitude. Attenuating mitochondrial Ca 2+ efflux using an NCXm inhibitor, CGP-37157 (1 μM), reduced the amplitude, duration and size of LCR. It also attenuated early LCR occurrence, and simultaneously prolonged LCR period and CL. Additionally, CGP-37157 reduced caffeine-induced Ca 2+ transient. Therefore, the inhibitory effect on LCR was attributable to the reduction of the SR Ca 2+ content through NCXm inhibition. No obvious off-target effects of 1 μM CGP-37157 were found on T- and L-type voltage-gated Ca 2+ currents and hyperpolarization-activated inward current. Taken together, these results suggest that mitochondria are involved in LCR generation by modulating the SR Ca 2+ content through NCXm-mediated Ca 2+ efflux in murine SANCs. Graphical abstract: Unlabelled Image Highlights: LCR emerged near mitochondria in murine SA nodal cells. Inhibition of mitochondrial Ca2+ release attenuated LCR. Spatial and functional association of mitochondria with SR modulates LCR.